A PROSPECTIVE STUDY TO EVALUATE THE ROLE OF INTRAVENOUS TRANEXEMIC ACID IN REDUCING THE BLOOD LOSS DURING TOTAL KNEE ARTHROPLASTY - BAKSHI, AMANDEEP SINGH; MEHTA, HARRY; RAINA, SUKHIL; SAHNI, GIRISH; GERA, KARAN (International Journal of Current Pharmaceutical Research, 2024)
Objective: The goal of this research was to determine how well intravenous tranexamic acid works in minimizing excessive bleeding after total knee arthroplasty. Methods: The study was done on 50 patients of different age groups. Patients were randomly separated into two groups of 25 each. Group 1 were those who received intravenous tranexamic acid and group 2 were those who did not receive intravenous tranexamic acid. SPSS software was used to keep track of everything that happened and assess the outcomes. Results: Patients in Group A had a mean perioperative blood loss of 298.04 ml, whereas those in Group B lost 447.2 ml on average after surgery. When comparing the two groups statistically, it was shown that group A had considerably larger mean perioperative blood loss than group B. Conclusion: Patients in group B had substantially lower mean hemoglobin than patients in group A at the postoperative day 1 and postoperative day 7 measurements.